DIGITAL SKILLS OF TEACHERS FOR LIFELONG LEARNING - ROMANIAN REALITIES AND PERSPECTIVES - Alexandrina Mihaela POPESCU (Universitaria Publishing House, Craiova, 2020)
The need for teacher's Lifelong learning is a permanent and paramount goal of any 21st-century education system and the best investment that any state can make to ensure the social, economic and cultural future. The European Union has shown an increased interest in training and developing the digital skills of teachers in the European area in recent years. In this regard, EU has developed a series of measures and recommendations for Member States. Nevertheless, in Romania we are experiencing a crisis caused by the shift of teaching activities to the online environment, the lack of digital skills of teachers in pre-university education and, last but not least, the lack of digital media (free internet access, computers, tablets) for a large part of the students. The current paper aims to identify the Romanian context shaping the development of the teachers' digital skills for Lifelong Learning up to the onset of lockdown, which led to the relocation of teaching activities online (on 16 March 2020), also focusing on the measures taken during lockdown (16 March 16 - 15 May 2020). The question we are trying to answer is how prepared were the teachers to cope with the online teaching activities, how much had the schools advanced in the integration of digital resources to face-to-face teaching.